Sepsis‐induced expansion of granulocytic myeloid‐derived suppressor cells promotes tumour growth through Toll‐like receptor 4. Issue 4 (23rd June 2016) - Llitjos, Jean‐François; Auffray, Cédric; Alby‐Laurent, Fanny; Rousseau, Christophe; Merdji, Hamid; Bonilla, Nelly; Toubiana, Julie; Belaïdouni, Nadia; Mira, Jean‐Paul; Lucas, Bruno; Chiche, Jean‐Daniel; Pène, Frédéric
Abstract: Severe sepsis remains a frequent and dreaded complication in cancer patients. Beyond the often fatal short‐term outcome, the long‐term sequelae of severe sepsis may also impact directly on the prognosis of the underlying malignancy in survivors. The immune system is involved in all stages of tumour development, in the detection of transforming and dying cells and in the prevention of tumour growth and dissemination. In fact, the profound and sustained immune defects induced by sepsis may constitute a privileged environment likely to favour tumour growth. We investigated the impact of sepsis on malignant tumour growth in a double‐hit animal model of polymicrobial peritonitis, followed by subcutaneous inoculation of MCA205 fibrosarcoma cells. As compared to their sham‐operated counterparts, post‐septic mice exhibited accelerated tumour growth. This was associated with intratumoural accumulation of CD11b + Ly6G high polymorphonuclear cells (PMNs) that could be characterized as granulocytic myeloid‐derived suppressor cells (G‐MDSCs). Depletion of granulocytic cells in post‐septic mice inhibited the sepsis‐enhanced tumour growth. Toll‐like receptor (TLR)‐4 (Tlr4) and Myd88 deficiencies prevented sepsis‐induced expansion of G‐MDSCs and tumour growth. Our results demonstrate that the myelosuppressive environment induced by severe bacterial infections promotes malignant tumour growth, and highlight a critical role of CD11b + Ly6G high G‐MDSCs under the control of TLR‐dependent signalling. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.